Overpopulation and communicable disease occurrence among students in secondary schools in Ibadan, Oyo State (2008)
Class size in every school system all over the world is very important with respect to the health status of students in the school. In Nigeria, large classes consist of classrooms with more than the maximum acceptable standard of forty student par class. Large classes therefore are likely to put students at greater risk of injury, reduce learning and increase the possibility of contracting infectious diseases. Other conditions include nutrition, personal hygiene, environmental sanitation, the quality of school building and health care services available in schools, that would influence the health of students. It is however a fact that students come to school with a lot of health problems most of which are infectious in nature and are transmissible through contact especially in an overpopulated classroom. The study therefore, examines the effect of overpopulation on the occurrence of communicable diseases in secondary schools in Ibadan, Oyo State. A sample of one thousand (1000) respondents were used for the study. Data were collected using questionnaire while data analysis involved the use of frequency counts and percentages. The result showed that overpopulation predisposed student to communicable diseases. The findings have implications for policy makers, educators and all stake holders interested in the health and well being of students.